Combined Deficiency of Coagulation Factors V and VIII: An Update - Zheng, Chunlei; Zhang, Bin (Seminars in Thrombosis and Hemostasis, 2013)
Combined deficiency of factor V (FV) and FVIII (F5F8D) is an autosomal recessive bleeding disorder characterized by simultaneous decreases of both coagulation factors. This review summarizes recent reports on the clinical presentations, treatments, and molecular mechanism of F5F8D. Genetic studies identified LMAN1 and MCFD2 as causative genes for this disorder, revealing a previously unknown intracellular transport pathway shared by the two important blood coagulation factors. LMAN1 and MCFD2 form a Ca2+-dependent cargo receptor complex that functions in the transport of FV/FVIII from the endoplasmic reticulum (ER) to the Golgi. Disrupting the LMAN1-MCFD2 receptor, complex formation is the primary molecular defect of missense mutations leading to F5F8D. The EF-hand domains of MCFD2 are necessary and sufficient for the interactions with both LMAN1 and FV/FVIII. Similarly, the carbohydrate recognition domain of LMAN1 contains distinct and separable binding sites for both MCFD2 and FV/FVIII. Therefore, FV and FVIII likely carry duel sorting signals that are separately recognized by LMAN1 and MCFD2 and necessary for the efficient ER-to-Golgi transport. FV and FVIII likely bind LMAN1 through the high-mannose N-linked glycans under the higher Ca2+ conditions in the ER and dissociate in the lower Ca2+ environment of the ER–Golgi intermediate compartment.
Keywords: hemorrhagic disorders; ERGIC; protein trafficking; carbohydrate binding; calcium binding